2021
DOI: 10.1016/j.heliyon.2021.e08079
|View full text |Cite
|
Sign up to set email alerts
|

Assessing diabetes mellitus knowledge among Syrian medical students: A cross-sectional study

Abstract: Background: Diabetes mellitus is the fastest growing global health emergency of the 21st century. The Middle East and North Africa region have the highest prevalence of diabetes in the world. Since medical students are the pillars of future healthcare systems, their knowledge of the disease must be evaluated, updated, and enhanced appropriately. Methods: A cross-sectional study was conducted at the Syrian Private University (SPU) in November 2019 on World Diabetes Day in Damascus, during the Syrian war crisis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 39 High prevalence of T2D was observed in the refugee population studied. This prevalence is significantly higher than that in the general Syrian population 40 as well as in the Lebanese population 41 where the Syrian refugee population under study is currently living. Likewise, a nearly 2.5-fold increase in the prevalence of pre-diabetes was observed in the Syrian refugee population when compared with the general Syrian population and the host Lebanese population.…”
Section: Discussionmentioning
confidence: 64%
“… 39 High prevalence of T2D was observed in the refugee population studied. This prevalence is significantly higher than that in the general Syrian population 40 as well as in the Lebanese population 41 where the Syrian refugee population under study is currently living. Likewise, a nearly 2.5-fold increase in the prevalence of pre-diabetes was observed in the Syrian refugee population when compared with the general Syrian population and the host Lebanese population.…”
Section: Discussionmentioning
confidence: 64%
“…Depending on the clinical symptoms of DM can have a variety of clinical presentations, ranging from asymptomatic to significant consequences. The correct answer have modest variances, from Syrian study (21). Polydipsia, mouth dryness, fatigue, delayed wound healing, recurrent infections, and polyphagia (79.38% 88.16%, 83.13%, 73.13%, 72.5%, 73.13% verses 94.9%, 89.8%, 78.9%, 88.4%, 66.9%, 55.3%) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Only 37.8% correctly identified that a fasting plasma glucose level of 126 mg/dl or above is diagnostic for diabetes. Similarly, only 36.7% correctly identified that an HbA1c level of 6.4% or above indicates diabetes and only 34.2% correctly identified that an oral glucose challenge after two hours or a random plasma glucose level of 200 mg/dl or above is diagnostic for diabetes [ 9 ]. Though the risk of developing DM is higher in the older population, the young population is still at risk, which could be attributed to non-healthy lifestyles on a background of genetic predisposition.…”
Section: Introductionmentioning
confidence: 99%